Microbiomes of the built environment: a systematic literature review - Joseph, Tania M.; Abdulmaksoud, Sara; Mortula, Md. Maruf; Beheiry, Salwa; Zareen, Nausheen (Frontiers in Built Environment, 2025)
This systematic literature review explores the critical role of microbiomes in the built environment (MoBE) and their impact on public health, particularly in pathogen transmission and infection control. Microbial communities in indoor and outdoor spaces are shaped by architectural design, ventilation, human occupancy, and other environmental factors. The COVID-19 pandemic has intensified the need to understand airborne, surface, waterborne, and other transmission pathways to mitigate disease spread. Despite advancements in microbial ecology, gaps remain in integrating findings with architectural and urban planning strategies. Future research should incorporate smart technologies, study long-term MoBE dynamics, explore sustainable building materials, and assess climate change impacts on microbial compositions. Strengthening policies on microbial risk management, air quality, and sanitation in high-occupancy environments, addressing these gaps, and fostering interdisciplinary collaboration will help create healthier, safer, and more resilient built environments aligned with global sustainability and public health goals.